1996
DOI: 10.1139/v96-115
|View full text |Cite
|
Sign up to set email alerts
|

Delocalized bonding in tetrahedral organo-transition metal clusters: an EHMO study of metal vertex rotations in Co2Fe(CO)9S, CpMoCo2(CO)8CR, and in Cp2Mo2(CO)4(RC≡CR)

Abstract: Molecular orbital calculations at the extended Huckel level are used to rationalize the baniers to vertex rotation in the tetrahedral metal cluster complexes F~CO,(CO)~S, 2, and (C5H5)MoCo,(CO),CH, 3. It is shown that, in accord with experimental observations on 2, rotation of an Fe(CO), fragment through 60' brings about a weakening of the metal-metal bonding interactions within the FeCo, triangle. In the MoCo, cluster, 3, rotation of the CpMo(CO), fragment about an axis joining the molybdenum to a central poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

1998
1998
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
1
1
Order By: Relevance
“…The NMR fluxionality of alkyne adducts of the type reported here has long been known 31 and a recent crystallographic and theoretical study 32 has elegantly implicated Mo(CO) 2 (η-C 5 H 5 ) vertex rotation in the equilibration. In the present work the geometry of the Mo(CO) 2 (η-C 5 H 5 ) vertices is similar to that found in the preceding survey of 22 related vertices 32 where the Cp centroid ᎐Mo᎐CO angles were found to lie in a narrow range of 114.3 ± 3.7Њ. These workers applied a Bürgi-Dunitz analysis of the trajectory of the ring centroid associated with the molybdenum cyclopentadienyl fragment to a number of crystallographically characterised compounds and concluded that racemisation of these inherently chiral molecules proceeds via vertex rotation giving initially a molecule Complex 3a exhibits fluxional behaviour in solution, previously observed for simple alkyne adducts 31 and the complexes 5.…”
Section: Molecular Structures Of Complexes 3 and 4bsupporting
confidence: 84%
See 2 more Smart Citations
“…The NMR fluxionality of alkyne adducts of the type reported here has long been known 31 and a recent crystallographic and theoretical study 32 has elegantly implicated Mo(CO) 2 (η-C 5 H 5 ) vertex rotation in the equilibration. In the present work the geometry of the Mo(CO) 2 (η-C 5 H 5 ) vertices is similar to that found in the preceding survey of 22 related vertices 32 where the Cp centroid ᎐Mo᎐CO angles were found to lie in a narrow range of 114.3 ± 3.7Њ. These workers applied a Bürgi-Dunitz analysis of the trajectory of the ring centroid associated with the molybdenum cyclopentadienyl fragment to a number of crystallographically characterised compounds and concluded that racemisation of these inherently chiral molecules proceeds via vertex rotation giving initially a molecule Complex 3a exhibits fluxional behaviour in solution, previously observed for simple alkyne adducts 31 and the complexes 5.…”
Section: Molecular Structures Of Complexes 3 and 4bsupporting
confidence: 84%
“…30-32 A number of processes are thought to occur: (1) a relatively low-energy process interchanges semibridging and terminal CO groups on the molybdenum vertices and (2) a higher-energy process equilibrates the C 5 H 5 groups on the Mo atoms, which is thought to occur with some degree of vertex rotation. 32 In the present work the alkyne is unsymmetrical and as such we have not reached the slow exchange limit at the lowest temperature measured, in spite of the steric demand of the alkyne. The Fig.…”
Section: Molecular Structures Of Complexes 3 and 4bcontrasting
confidence: 48%
See 1 more Smart Citation